1993
DOI: 10.1002/hlca.19930760505
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Aristotelia‐Type Alkaloids. Part XII. Total synthesis of (−)‐tasmanine. Stereoelectronic factors that control the rearrangement of 3H‐indol‐3‐ol derivatives to oxindoles ( = 1,3‐dihydro‐2H‐indol‐2‐ones) or to pseudoindoxyls ( =1,2‐dihydro‐3H‐indol‐3‐ones)

Abstract: The oxidative transformation of (+)‐aristoteline ((+)‐5) into its metabolites, the recently synthesized indole alkaloids (−)‐serratoline ((−)‐6), (+)‐aristotelone ((+)‐2), and (−)‐alloaristoteline ((−)‐22), was investigated in more detail. It was demonstrated that the diastereoface selectivity of the reaction of (+)‐5 with 3‐chloroperbenzoic acid can be altered by variation of the solvent as well as by addition of CF3COOH. The chemoselectivity of the 1,2‐rearrangement of the intermediate 3H‐indol‐3‐ol derivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…[17] Subjecting 22 to the one-pot double bond cleavage/cyclization sequence established for the conversion of 20 a into 21 (see Scheme 4) provided heptacyclic compound 23 whose NMR spectra were significantly different from those of terengganensine A. We reasoned that, upon formation of dialdehyde 24,the nitrogen N1 would attack, as aresult of the geometric constraint, the C20 equatorially oriented CH 2 CHO functional group (C18) leading to hemiaminal 25 that would further cyclize to heptacycle 23.S ince both hemiaminal and acetal formation is reversible and the configurations at the C2 and C7 positions in 23 are in principle adjustable under acidic conditions,c ompound 23 was subsequently treated with ad iverse set of Lewis acids and Brønsted acids.H owever, only recovery or decomposition of the starting material was observed.…”
Section: Angewandte Chemiementioning
confidence: 97%
See 1 more Smart Citation
“…[17] Subjecting 22 to the one-pot double bond cleavage/cyclization sequence established for the conversion of 20 a into 21 (see Scheme 4) provided heptacyclic compound 23 whose NMR spectra were significantly different from those of terengganensine A. We reasoned that, upon formation of dialdehyde 24,the nitrogen N1 would attack, as aresult of the geometric constraint, the C20 equatorially oriented CH 2 CHO functional group (C18) leading to hemiaminal 25 that would further cyclize to heptacycle 23.S ince both hemiaminal and acetal formation is reversible and the configurations at the C2 and C7 positions in 23 are in principle adjustable under acidic conditions,c ompound 23 was subsequently treated with ad iverse set of Lewis acids and Brønsted acids.H owever, only recovery or decomposition of the starting material was observed.…”
Section: Angewandte Chemiementioning
confidence: 97%
“…[16] After having screened over fifty conditions,t he desired transformation was finally realized with meta-chloroperbenzoic acid (mCPBA) in CH 2 Cl 2 in the presence of an excess of trifluoroacetic acid (TFA) at À78 8 8C( Scheme 5). [17] Under these conditions,c ompound 22 was isolated in 95 %y ield as as ingle isomer.A lthough it is difficult to assign the stereochemistry at the C7 position with certainty,w e observed that the 1 HNMR spectrum of 22 was significantly different from that of 20 a and 20 b (for details,s ee the Supporting Information) and tentatively concluded that the hydroxylation occurred from the sterically less accessible aface of the C2=C7 double bond. Such unusual stereoselectivity could be explained by invoking the intermediate A in which ah ydrogen-bonding interaction between the ammoni- …”
mentioning
confidence: 99%
“…[17] Subjecting 22 to the one-pot double bond cleavage/cyclization sequence established for the conversion of 20 a into 21 (see Scheme 4) provided heptacyclic compound 23 whose NMR spectra were significantly different from those of terengganensine A. [17] Subjecting 22 to the one-pot double bond cleavage/cyclization sequence established for the conversion of 20 a into 21 (see Scheme 4) provided heptacyclic compound 23 whose NMR spectra were significantly different from those of terengganensine A.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Communications um salt and mCPBAd irected the reaction trajectory. [17] Subjecting 22 to the one-pot double bond cleavage/cyclization sequence established for the conversion of 20 a into 21 (see Scheme 4) provided heptacyclic compound 23 whose NMR spectra were significantly different from those of terengganensine A. We reasoned that, upon formation of dialdehyde 24,the nitrogen N1 would attack, as aresult of the geometric constraint, the C20 equatorially oriented CH 2 CHO functional group (C18) leading to hemiaminal 25 that would further cyclize to heptacycle 23.S ince both hemiaminal and acetal formation is reversible and the configurations at the C2 and C7 positions in 23 are in principle adjustable under acidic conditions,c ompound 23 was subsequently treated with ad iverse set of Lewis acids and Brønsted acids.H owever, only recovery or decomposition of the starting material was observed.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…However,w eh oped that the subsequent formation of the C18O À C2 bond would be kinetically fast enough to drive the reaction towards the formation of the natural product (AE)-4.I ti sw orth noting that conversion of 2,2-disubstituted indolin-3-one into 3,3-disubstituted indolin-2-one by double 1,2-alkyl migration with concurrent 1,2-shift of the carbonyl group is known [20] and has been elegantly exploited in the synthesis of aristotelia-type indole alkaloids. [21] Ther ealization of the aforementioned transformation turned out to be ademanding task. After screening different Brønsted acids (TFA, p-TsOH·H 2 O, MsOH) and Lewis acids [BF 3 ·Et 2 O, BCl 3 ,S c(OTf) 3 ,C u(OTf) 2 ,e tc.…”
mentioning
confidence: 99%